PERANCANGAN PENCETAK DAN MIXER PADA MESIN PENCETAK PAKAN TERNAK DENGAN KONSEP 2 IN 1 - Jatira; TB. Utami Adi Subekhi; Gugun Gunawan (Sekolah Tinggi Teknologi Wastukancana, 2021)
The development of technology has helped manking in faciliting a job. One of them is for chicken farmers, many machine are used to process chicken feed. But machines that have a simple processing system and minimalist design are still rarely found. Many people who work as breeders but still have difficulty processing chicken feed, therefore it is neccesarry to design and build machines that can process the chicken feed. This cattle feed printing machine with the 2 in 1 namely mixing and printing in one machine is a solution to overcome these problems and supports farmers in feed processing, in addition to an easy processing system, namely by mixing raw materials into a mixer, then the raw materials will printed on a printer and comes out in the form of pellets. This printing machine is capable of producing 60 kg of pellets in one hour from the previous only producing 20 kg of pellets in one hour. This animal feed printing machine uses electrical energy and its minimalist shape does not tke up much processing space, which is practical and efficient. Pellets are a form of artificial food made from mixtures,materials or components, then mixed and printed in the form of small sticks. The main source of feed available for animal husbandry must be adequate and can meet the needs for chicken farming.